The upcycling of waste medical plastic from the health care sector - DANIEL HARMAN (2022)
The aim of this research is to find if it is possible to take a Confidence BE stoma bag, dissolve it in a solvent (or solvent mixture) and then use the resulting solution to synthesis carbon nanotubes. CNTs can have numerous applications but the aim is to convert them into electrical wires due to the very high charge carrying capacity of CNTs1. The idea is to recycle the stoma bags to achieve a circular economy within SALTs healthcare. The recycling of the stoma bags will also help to start tackling the problem with plastic pollution. Toluene and M cresol were used as solvents to attempt to dissolve the different plastics the stoma bags are made up from. The temperature, stirring speed and particle size were manipulated to attempt to find the most suitable ways to complete dissolution of the stoma bag. COMSOL Multiphysics was utilised after the lab had to be closed to attempt to simulate the dissolution. Both the lamina flow and transport of dilute species modules were used in the simulations that were run to attempt to model dissolution. Carbon nanotubes have been synthesised from pure toluene, pure m-cresol, commercial grade toluene, and a solution of Low-density polyethylene (LDPE) dissolved in toluene. Various different growth conditions were used in the synthesis of the CNT and the highest mass produced was, 0.2674 g (EXP 3, Table 6). This mass of CNT was synthesised from toluene and LDPE. 3 different ways for calculating the heat of formation of the CNTs were used, the answers are vastly different as are the methods and it is difficult to determine which value is the most accurate. A SEM and Raman spectroscopy have been used to attempt to find the quality and quantity of some of the CNT samples, the results can be seen in Appendix I & II to draw proper conclusions about the quality and quantity of CNTs produced more analysis would be needed. The overall conclusion that I have been able to draw from the research that I have completed for this thesis is that the dissolution of the stoma bag and then the conversion of the resulting solution into CNTs is a viable method of recycling the stoma bag. While there are still some creases that need to be ironed out with regards to the best method for scale up and the most effective temperatures and either flow velocities or agitation speeds for the dissolution, it is clear to see that CNTs can and have been produced and these CNTs can be used for a vast range of different applications. The initial aim of the research was to upcycle waste medical plastic, and this has been completed throughout the course of this research so I can conclude that this method of upcycling the stoma bags supplied by SALTs Healthcare is a valid method.